Walking the financialized city: confronting capitalist urbanization through mobile popular education. (23rd September 2020) - Silver, Jonathan; Fields, Desiree; Goulding, Rich; Rose, Isaac; Donnachie, Siobhan
Abstract: How do communities understand the highly abstract process of housing financialization? In this paper we argue that walking tours offer the capacity to develop new forms of mobile, public education to learn about the capitalist urbanization process, especially as the financialization of housing accelerates. Based on walking the city of Manchester we show that this type of learning may improve public literacy concerning the opaque and extended ways in which housing in central areas has increasingly been shaped by new types of real estate finance. Although many people in Manchester have understood the outline of these dramatic transformations, and could connect the new skyscrapers to their struggles for everyday survival, there remained a gap in detailed literacy of the actors, finances and dynamics that had changed the city so quickly. We contextualize the rapidly changing global landscape of housing since the global financial crisis of 2008 before showing how these transformations have reshaped housing in Manchester. We then describe the motivations for developing the tour, and the details of the walk itself. We conclude by suggesting that the walking tour offers new types of possibility in necessary learning and subsequent action to address capitalist urbanization.